Self-incompatibility genes of Brassica oleracea: Expression, isolation, and structure - Nasrallah, June B. (1988)
We demonstrate by in situ hybridization the cell-type-specific expression of transcripts encoded by the self-incompatibility (S) locus of Brassica oleracea. These transcripts are not detected early in stigma development, their expression is switched on in the papillar cells of the stigma surface, and their levels increase in these cells in correlation with the acquisition by the stigma of the self-incompatibility response. By using a probe derived from the untranslated sequences at the 3′ end of S cDNA, an S-gene copy expressed in the papillar cells has been isolated from among the multiple S-related copies that occur in the Brassica genome. Structural analysis of this gene shows that it lacks introns. In light of the strict spatial and temporal regulation of S-gene expression in precisely the cells that constitute the barrier to self-pollination, the self-incompatibility response may be viewed as a cell-cell interaction between one pollen grain and one papillar cell.